The sustainability of upper limb robotic therapy for stroke survivors in an inpatient rehabilitation setting. Issue 24 (20th November 2022) - Flynn, Nicholas; Froude, Elspeth; Cooke, Deirdre; Dennis, Jessica; Kuys, Suzanne
Abstract: Purpose: To investigate the sustainability of Robot-assisted upper limb therapy (RT-UL) as part of routine occupational therapy and physiotherapy clinical practice. Methods: Two separate audits, 12 months apart, of RT-UL computer data records were undertaken to determine sustainability in a subacute rehabilitation unit. Records of the two audits were compared in terms of the number of early subacute stroke survivors using RT-UL, the number of RT-UL sessions, duration of RT-UL sessions, and disciplines prescribing RT-UL. Results: During Audit 1 58% ( n  = 18) of stroke survivors received RT-UL compared to 50% ( n  = 7) in Audit 2. The total number of RT-UL sessions reduced between audits (148 vs. 36 sessions) reflecting the overall reduction in admission rates for stroke survivors. There was no significant difference between audits in the average number of RT-UL sessions per patient ( p  = 0.203) nor the length of sessions ( p  = 0.762). Patients engaged in active therapy more than three-quarters of the time when on the robotic device. Physiotherapists were the primary prescribers of RT-UL when compared to occupational therapists. Conclusions: RT-UL was in continued and regular use with stroke survivors 2 years after initial implementation within an inpatient rehabilitation setting. RT-UL practice was intensive and used routinely with patients. IMPLICATIONS FOR REHABILITATION: RT-UL is a sustainable and intensive intervention for stroke survivors within an inpatient rehabilitative setting. The cost-benefits of RT-UL should be evaluated from the perspective of the whole rehabilitation service not just at an individual patient level. RT-UL may be considered a "bridging" form of UL practice for those with more limited active UL movement until there is sufficient UL movement and power for more complex real-world task-specific practice.